Measurement of surface velocity in open channels using a lightweight remotely piloted aircraft system. Issue 1 (1st January 2017) - Bolognesi, M.; Farina, G.; Alvisi, S.; Franchini, M.; Pellegrinelli, A.; Russo, P.
ABSTRACT: In this paper, a low-cost remotely piloted aircraft system (RPAS) technique is proposed for measurement of the surface velocity in rivers or channels with low surface velocity and small discharge. To verify the reliability of the results obtained with the RPAS, we simultaneously measured the surface velocity with other methods based on total stations and close range photogrammetry. The RPAS was used both with ground control points (GCPs) for orientation of the photographic images and without GCPs. The data analysis showed that the RPAS provides valid results even without GCPs. Use of a RPAS without GCPs, relying solely on flight altitude to determine the water velocity, opens the way for its utilization in emergency conditions when it is impossible to access the river banks for the realization and survey of GCPs.